The Utility of Teleultrasound to Guide Acute Patient Management. Issue 3 (May 2017) - Becker, Christian; Fusaro, Mario; Patel, Dhruv; Shalom, Isaac; Frishman, William H.; Scurlock, Corey
Abstract : Ultrasound has evolved into a core bedside tool for diagnostic and management purposes for all subsets of adult and pediatric critically-ill patients. Teleintensive care unit coverage has undergone a similar rapid expansion period throughout the United States. Round-the-clock access to ultrasound equipment is very common in today's intensive care unit, but 24/7 coverage with staff trained to acquire and interpret point-of-care ultrasound in real time is lagging behind equipment availability. Medical trainees and physician extenders require attending level supervision to ensure consistent image acquisition and accurate interpretation. Teleintensivists can extend the utility of ultrasound by supervising and guiding providers without or with only partial training in ultrasound, and also by extending direct trainee ultrasound supervision to time periods when no direct bedside attending supervisor is available, and when treatment decisions otherwise would have been made without supervision and feedback on image acquisition and interpretation. Nursing staff without ultrasound training can also be directed to perform basic ultrasound exams, which may have immediate diagnostic and/or treatment consequences, thereby overcoming access barriers in the absence of physicians or physician extenders. We discuss 4 real-life clinical scenarios in which teleintensivist supervision extended and standardized bedside ultrasound exams to guide management decisions which significantly impacted patient outcomes.